COMMUNICATION MODELS: GENESIS AND THE MODERN STATE - Prysyazhnyuk, Petrо (Pressing Problems of Public Administration, 2019)
The article deals with the development of theoretical models of communication. The paper analyzed the models of communication in the socio-economic context and determined the factors influencing the evolution of the scientific vision of the communication process in public administration. The author has identified trends in the development of theoretical modeling of the communication process.This article basic information on the communication models of Lasswell H. D., Shannon C. E. and Weaver W., Westley and MacLean, Braddock R., de Fleur, Dance, Schramm W., Maletzke G., Buhtaty O. E., etc. is presented. These theoretical models are also analyzed. The paper notes that in scientists gradually complicated the structure of communication models: from one level to several, from immediacy to mediocrity. According to the author, the rapid development of social psychology during the 1950s led to a rethinking of communication. In the second half of the twentieth century, the results of research by sociologists, psychologists, marketers, etc., created an increasingly complex mosaic picture of social, including communicative, relationships.The author notes that it was urgent to create a large-scale model that would reproduce a complex common system of communicative relations in society. Such a theoretical construction should be of several levels and should have horizontal and vertical directions of information transmission.The author predicts a continuous complication of communication models with the further development of various branches of science. So, the time of simple communication models has passed.